Bias‐Modulated Multicolor Discrimination Enabled by an Organic–Inorganic Hybrid Perovskite Photodetector with a p‐i‐n‐i‐p Configuration. Issue 11 (11th September 2020) - Kim, Hyeonghun; Kim, Woochul; Pak, Yusin; Yoo, Tae Jin; Lee, Hae‐Won; Lee, Byoung Hun; Kwon, Sooncheol; Jung, Gun Young
Abstract: Despite significant progress in color discrimination in various optoelectronic systems, most conventional technologies equipped with dissipative optical filters still suffer from high incident light loss and costly manufacturing. Herein, it is demonstrated that a novel class of organic–inorganic hybrid perovskite photodetectors based on a p‐i‐n‐i‐p structure can exhibit a switchable spectral response caused by bias modulation. A single photodetector with a p‐i‐n‐i‐p structure in which a low‐band n‐i‐p perovskite diode is vertically stacked on top of a high‐band p‐i‐n perovskite diode allows selective charge extraction from each perovskite diode by switching the bias polarity, resulting in fine discrimination of monochromatic red (R), green (G), and blue (B) light. Furthermore, a combination of two p‐i‐n‐i‐p photodetectors is successfully applied for identifying an arbitrary nonmonochromatic color (i.e., a mixed color in RGB space); thus, this approach can pave the way for developing spatially efficient and optical filter‐free imaging systems. Abstract : A novel perovskite photodetector with a p‐i‐n‐i‐p device configuration comprising low‐band n‐i‐p and high‐band p‐i‐n diodes exhibits a bias‐switchable spectral response, enabling discrimination of monochromatic visible light without supplementary color filters. Furthermore, a combination of two p‐i‐n‐i‐p photodetectors successfully discriminates arbitrary nonmonochromatic colors, suggesting spatially efficient and color filter‐free imaging systems.